Regulation and Financial Performance of Commercial Banks in Kenya - Wanja, Helen (University of Embu, 2020)
The study sought to evaluate the effect of regulation on financial performance of commercial banks in Kenya. To achieve this the study evaluated effect of capital adequacy and liquidity regulation ratio on the financial performance of commercial banks in Kenya. The problem was that despite the regulations set by the CBK there have been reported cases of failure of banks and there have also been banks consistently showing negative profits in their financial statements. The study focused on the 43 commercial banks. The study sampled six commercial banks. Secondary data was used which was drawn from the banks audited financial statement found on the bank’s websites and central bank of Kenya website. The data was analyzed using reviews 9 software. Descriptive statistics and regression analysis was used to analyze the data. The findings indicated that capital adequacy has a positive relationship with financial performance of commercial banks while liquidity regulation has a negative relationship with performance of commercial banks in Kenya. The study recommended that central bank of Kenya imposes strict regulations in order to identify banks that are struggling and give necessary actions to be taken in advance to prevent collapse of banks.